Historical trends in iodine and selenium in soil and herbage at the Park Grass experiment, Rothamsted Research, UK - Bowley, Hannah E.; Mathers, Andrew W.; Young, Scott D.; MacDonald, Andy J.; Ander, E. Louise; Watts, Michael J.; Zhao, Fangjie J.; McGrath, S.P.; Crout, Neil J.M.; Bailey, Elizabeth H. (Wiley, 2017)
Long term trends in iodine and selenium retention in soil, and uptake by herbage, were investigated in archived samples from the Park Grass Experiment, initiated in 1856 at Rothamsted, UK. Soil (0-23 cm) and herbage samples from plots receiving various mineral fertilisers and organic manures, with and without lime, were analysed for Se and iodine (I) to assess the effect of soil amendment, annual rainfall, crop yield and changes in soil chemistry from 1876 to 2008. Comparing soil from limed and un-limed control (unfertilized) plots, TMAH-extractable Se and I concentrations both diverged, with time, with greater retention in un-limed plots; differences in concentration amounted to 92 and 1660 µg kg-1 for Se and I respectively after 105 yr. These differences were broadly consistent with estimated additions from rainfall and dry deposition. Offtake of both elements in herbage was negligible compared to soil concentrations and annual inputs (<0.003% of total soil I and <0.006% of total soil Se). A positive correlation was observed between I and Se concentrations in herbage, suggesting some common factors controlling bioavailability. A growth-dilution effect for I and Se was suggested by the positive correlation between growing season rainfall (GSR) and herbage yield together with soil-to-plant transfer factors decreasing with yield. Phosphate and sulphate fertilizers reduced I and Se herbage concentrations, both through ion competition and increased herbage yield. Results suggest that in intensive agriculture with soil pH control, the I requirement of grazing animals is not likely to be met by herbage alone.